2022
DOI: 10.3389/fbioe.2022.965209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PaGLK transgenic poplar on microbial community and soil enzyme activity in rhizosphere soil

Abstract: Rhizosphere microorganisms are essential parts in maintaining soil ecological functions. Reforestation using genetically modified trees might have great potential to enhance tree production in biotic and abiotic stress, however, their long-term impact on rhizosphere microorganisms is scant. In this study, we studied soil enzyme activities and composition of rhizosphere microorganisms in 2-year-old transgenic PaGLK overexpression (OE), repressed expression (RE) and wild-type (WT) poplar (P. alba × P.berlinensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…When transgenic maize with a cloned Cry1Ah gene from B. thuringiensis was grown, no significant differences were found in the bacterial composition of the rhizosphere, but the metabolic profile was altered, with most of the altered metabolites being related to the metabolism of the plant itself rather than the pathways of the plant-bacteria relationship [363]. A similar result was obtained when growing the genetically modified potato variety Modena, tubers of which have altered starch content, but in this case, it is likely that the modulation of the microbial community was due to root exudate [364], which was also observed in an experiment on transgenic poplars [365]. Overall, a number of studies confirmed that rhizosphere composition can change only slightly, but the outcome still depends on which genes and metabolic pathways were involved [366][367][368].…”
Section: Problems and Perspectives Related To The Application Of Geno...supporting
confidence: 65%
“…When transgenic maize with a cloned Cry1Ah gene from B. thuringiensis was grown, no significant differences were found in the bacterial composition of the rhizosphere, but the metabolic profile was altered, with most of the altered metabolites being related to the metabolism of the plant itself rather than the pathways of the plant-bacteria relationship [363]. A similar result was obtained when growing the genetically modified potato variety Modena, tubers of which have altered starch content, but in this case, it is likely that the modulation of the microbial community was due to root exudate [364], which was also observed in an experiment on transgenic poplars [365]. Overall, a number of studies confirmed that rhizosphere composition can change only slightly, but the outcome still depends on which genes and metabolic pathways were involved [366][367][368].…”
Section: Problems and Perspectives Related To The Application Of Geno...supporting
confidence: 65%
“…Salas-González et al investigated the regulatory relationship between the root diffusion barriers in the endodermis and microbiota and found that genes controlling endodermal function in Arabidopsis thaliana contribute to the plant microbiome assembly [30]. Previous studies have shown signi cant differences in the activity of bacteria, fungi, and soil enzymes in the roots of transgenic poplar lines with overexpressed PaGLK, suppressed expression, and WT [21]. Furthermore, PaGLK gene expression alter the photosynthetic capacity of poplar [20].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a microenvironment by root secretions has signi cant implications, studies on root exudates in poplar is scarce. Our previous studies showed that suppression of PaGLK1 of Populus alba × P. Berolinensis reduces chlorophyll content and have effects on root exudates, rhizosphere soil enzyme activities and soil microbial community composition [20,21]. The root exudates primarily originate from plant photosynthesis.…”
Section: Introductionmentioning
confidence: 99%